Correction: In vivo treatment with a non-aromatizable androgen rapidly alters the ovarian transcriptome of previtellogenic secondary growth coho salmon (Onchorhynchus kisutch). - Christopher Monson; Giles Goetz; Kristy Forsgren; Penny Swanson; Graham Young (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0311628.].